Bystander evil and upstander intervention: the stories of Job and Jesus - Ki, Magdalen Wing-chi (Critical research on religion, 2025)
Perpetrators are committed to wrongdoing due to four types of evils: individual, diabolical, superego, or institutional evil. Yet bystanders can be just as problematic. First, classic “bystander effect” is often linked to individual or ego-evil. Second, the dark side of human nature can advance bystander diabolism. Third, a law-abiding subject may be (mis)guided by their superego, taking comfort in inhuman bystander legalism. Fourth, institutional dynamics can spearhead bystander groupthink. The stories of Job and Jesus show that bystanders—whether active, passive, or interactive—often play an important role in human affairs. In the darkest hours, individuals can battle bystander evil due to their different attachment patterns and coping methods, championing upstander interventions at the individual or collective level.